In a small room I wait - Madore, Melissa (Department of English Language and Literature, 2014)
Me. Watch me. It's me. Can you see me? Look I am running now, and I can run fast, as fast as a car, you don't believe me? Watch me. Now, I am going to throw this ball to you, are you going to catch it? Catch it. Don't let it fall. Don't let it fall.